2004
DOI: 10.1039/b308033a
|View full text |Cite
|
Sign up to set email alerts
|

Bimolecular processes on silica gel surfaces: energetic factors in determining electron-transfer rates

Abstract: Triplet state and radical cation formation is observed following laser excitation of anthracene, phenanthrene and naphthalene (and their derivatives) adsorbed on silica gel. Energy- and electron-transfer reactions of these compounds with co-adsorbed azulene have been studied using a time-resolved diffuse reflectance laser flash photolysis technique. Triplet energy transfer from the arene derivative to azulene and electron transfer from azulene to the arene radical cation have been investigated in order to dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(43 citation statements)
references
References 68 publications
2
39
2
Order By: Relevance
“…Energetics were also demonstrated to have a significant role in determining electron transfer rates 2,6 , and we have shown a Marcus-type dependence of rate on the 45 free energy for electron transfer 2,6 . In these studies we have also found some evidence for an additional influence from steric factors 2 .…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Energetics were also demonstrated to have a significant role in determining electron transfer rates 2,6 , and we have shown a Marcus-type dependence of rate on the 45 free energy for electron transfer 2,6 . In these studies we have also found some evidence for an additional influence from steric factors 2 .…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown evidence for energy and electron transfer reactions in these systems as being largely dependent upon the rates of diffusion 2,3 , and in the case of 40 anthracene / azulene systems, rates of reaction are governed by the rate of diffusion of azulene which is more mobile than the anthracene moeities. Energetics were also demonstrated to have a significant role in determining electron transfer rates 2,6 , and we have shown a Marcus-type dependence of rate on the 45 free energy for electron transfer 2,6 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations